ENHANCING CARDIAC OPERATION THEATRE EFFICIENCY BY USING QUALITY CONTROL TOOLS IN CARDIAC SURGERY - Pervaiz, Farrah; Chaudhry, Imtiaz Ahmed; Zamir, Ali Gohar; Iqbal, Afsheen (Pakistan Armed Forces Medical Journal, 2015)
Objectives: To identify delays in the operative process in the cardiac surgery theatres. To understand the reasons of delay noted in different physes. Study Design: Descriptive cross sectional. Place and Duration of Study: AFIC/NIHD Rawalpindi from Dec 2015 to Jan 2015. Patients and Methods: A descriptive cross sectional study was conducted to analyze the cardiac surgery procedures, in terms of seven delays during three phases of operation theatre time utilization. Results: A total of 70 cases were analyzed. The mean time for anaesthesia induction and knife to skin time were estimated to be 29 min and 59 min respectively. All the time intervals are within the control limits. Maximum number of delays occurred during surgical procedure and sifting of the patient to the intensive care unit once the procedure ends, and is mainly attributable to shortage of experienced theatre staff and defective equipment. Conclusion: This study was performed in a tertiary cardiac care hospital and the time intervals of three phases of OT time utilization ranged within acceptable limits .The preparation of the equipment and required material for the OT cases must be done well in advance. It is essential that the anaesthetists and surgeons perform their work proficiently avoid undue delays, and supervise the proceedings as the OT managers. The QC tools can be aptly applied to all phases of operation theatre.